Effect of Alkaloids from Nelumbinis Plumula against Insulin Resistance of High-Fat Diet-Induced Nonalcoholic Fatty Liver Disease in Mice - Yong Xie; Yi Zhang; Zebin Guo; Hongliang Zeng; Baodong Zheng (Journal of Diabetes Research)
This study aimed to investigate the effects of total alkaloids from Nelumbinis Plumula (NPA) on insulin resistance (IR) of high-fat diet- (HFD-) induced nonalcoholic fatty liver disease (NAFLD). Rats were fed with HFD for 8 weeks to induce NAFLD. Then, the effect of NPA on ameliorating IR in HFD-induced NAFLD was evaluated. Fasting serum insulin was determined using an enzyme-linked immunosorbent assay (ELISA) kit for insulin following the manufacturer’s protocol. Some inflammatory cytokines such as tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6) were determined using ELISA kits to assess the inflammatory burden in rats. The results showed that HFD could induce a significant increase in blood glucose and IR in rats. However, rats treated with NPA (400 or 600 mg/kg) showed improved IR and reduction in serum inflammatory cytokines TNF-α and IL-6. Further investigation indicated that NPA could inhibit IR by restoring the insulin receptor substrate-1 (IRS-1) and suppressing the expression of c-Jun N-terminal kinase (JNK) phosphorylation. The present results supported the view that the pathogenesis of NAFLD was complex with inflammation, together with increasing serum glucose and IR. Also, JNK and IRS phosphorylation were suggested for their involvement in the modulating of IR during NAFLD progression. Therefore, NPA may serve as a potential natural remedy against IR in NAFLD.